REALIZATION OF RHYTHM IN POETRY “HUJAN BULAN JUNI” BY SAPARDI DJOKO DARMONO - Yusuf Adi Saputro; Yusi Anggraeni; Ida Lisdawati (PROJECT (Professional Journal of English Education), 2019)
The study aimed to determine the rhythm of the poetry The present study examined rhythm performed by the rhythm in the transcript of poetry Sapardi Djoko Darmono, title "Hujan Bulan Juni". A collection of poetry rhymes Sapardi Djoko Darmono published by Gramedia Widiasarana Indonesia Jakarta in 1994. The data were 12 distich  produced by all rhythm which performed in the poetry. Those rhythm were analyzed based on Schmitt dan Viala categories. Based on the result showed that césure (long pause) was the most frequent rhythm category. There were 12 of 12 distich of césure, 9 coupe and 2 enjambement . These results indicate that rhythm in the poetry had performed rhythm following Schmitt dan Viala  categories which had mention previously.